2012
DOI: 10.1016/j.sjbs.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological approaches for conservation and improvement of rare and endangered plants of Saudi Arabia

Abstract: Genetic variation is believed to be a prerequisite for the short-and long-term survival of the plant species in their natural habitat. It depends on many environmental factors which determine the number of alleles on various loci in the genome. Therefore, it is important to understand the genetic composition and structure of the rare and endangered plant species from their natural habitat to develop successful management strategies for their conservation. However, rare and endangered plant species have low gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 92 publications
0
32
0
5
Order By: Relevance
“…The flora of Saudi Arabia is faced with various threats such as deforestation, climate change, invasive species, altered soil pH and composition, stress due to various heavy metals, drought, salinity, high and low temperatures, different altitudes, and increased habitat fragmentation (Khan et al, 2012). The percentage of rare and endangered species is very high in Saudi Arabia as compared to other Middle East countries.…”
Section: Introductionmentioning
confidence: 99%
“…The flora of Saudi Arabia is faced with various threats such as deforestation, climate change, invasive species, altered soil pH and composition, stress due to various heavy metals, drought, salinity, high and low temperatures, different altitudes, and increased habitat fragmentation (Khan et al, 2012). The percentage of rare and endangered species is very high in Saudi Arabia as compared to other Middle East countries.…”
Section: Introductionmentioning
confidence: 99%
“…There are many biotechnological approaches available, which can be used to enhance its medicinal quality by increasing its content of phytoconstituents (Khan et al, 2012). Therefore, in the present study, sequence-based markers were developed for O. arabicus and further used for discrimination from a closely related species (O. baccatus), widely available in the Kingdom of Saudi Arabia, which share similar morphological characteristics in the dried state.…”
Section: Introductionmentioning
confidence: 99%
“…RNAi may help to improve the nutraceutical potential of a plant and/its products by enhancing the content of useful amino acids, fatty acids, fibre or by getting rid of allergenic/toxic compounds (Small 2007;Vaucheret 2006;Martino-Catt and Sachs 2008;Newell-McGloughlin 2008). Khan et al (2012) reported that RNAi is a potential technique being used for the production of medicinal plants with potential traits for a particular marker compound which is needed for eradication of diseases.…”
Section: Future Perspectivementioning
confidence: 99%